Performance, Genomic Rearrangements, and Signatures of Adaptive Evolution: Lessons from Fermentative Yeasts - Cubillos-Riffo, F (John Wiley and Sons Ltd, 2020)
The capacity of some yeasts to extract energy from single sugars, generating CO2 and ethanol (=fermentation), even in the presence of oxygen, is known as the Crabtree effect. This phenomenon represents an important adaptation as it allowed the utilization of the ecological niche given by modern fruits, an abundant source of food that emerged in the terrestrial environment in the Cretaceous. However, identifying the evolutionary events that triggered fermentative capacity in Crabtree-positive species is challenging, as microorganisms do not leave fossil evidence. Thus, key innovations should be inferred based only on traits measured under culture conditions. Here, we reanalyzed data from a common garden experiment where several proxies of fermentative capacity were recorded in Crabtree-positive and Crabtree-negative species, representing yeast phylogenetic diversity. In particular, we applied the “lasso-OU” algorithm which detects points of adaptive shifts, using traits that are proxies of fermentative performance. We tested whether multiple events or a single event explains the actual fermentative capacity of yeasts. According to the lasso-OU procedure, evolutionary changes in the three proxies of fermentative capacity that we considered (i.e., glycerol production, ethanol yield, and respiratory quotient) are consistent with a single evolutionary episode (a whole-genomic duplication, WGD), instead of a series of small genomic rearrangements. Thus, the WGD appears as the key event behind the diversification of fermentative yeasts, which by increasing gene dosage, and maximized their capacity of energy extraction for exploiting the new ecological niche provided by single sugars. © 2020 The Authors. Ecology and Evolution published by John Wiley & Sons Ltd.